Use of smart tensiometers for monitoring different deficit irrigation strategies in two young apple cultivars in Tunisia: comparison of physiological and pomological behavior - Bakri, Mourad; Guizani, Monia; Maatallah, Samira; Elloumi, Olfa; Rezig, Mourad (Frontiers in Agronomy, 2026)
Under climatic change and water scarcity conditions, the use of a precision irrigation system and crop-adapted irrigation strategy that takes into account climatic conditions is a major objective for scientists and farmers. The current study investigated the effects of different irrigation strategies, using low-cost smart tensiometers, on the vegetative growth, relative water content, gas exchange, and fruit quality of two young apple cultivars (Galaxy and Richared) in dry climate. Four irrigation treatments were considered: Control Irrigation [CI, 100% crop evapotranspiration (ETc)], Continuous Deficit Irrigation (CDI at 50% ETc), and Partial Root-zone Drying (PRD75 and PRD50 irrigated at 75% and 50% ETc, respectively). Results showed that shoot growth significantly decreased under CDI50% and PRD50% with a reduction of approximately 31.65% and 38.63% for Galaxy and Richared, respectively. A slight decrease in gas exchange parameters was recorded during the fruit ripening period, especially for Richared under CDI50% and PRD50%, while under PRD75%, the decrease was negligible. Moreover, a significant improvement in fruit quality was reported by an increase in firmness, TSS, that reached 19.50 and 17.50°Brix in Galaxy and Richared, respectively, under PRD75% and a decrease in acidity mainly in Richared. In conclusion, the deficit irrigation strategy PRD75% based on smart tensiometers data is the most recommended strategy in the region of the present study, considering its moderate effect on tree physiology and improvement in fruit quality.